Kinetics of Nanoparticle Interactions in Battery Electrodes. Issue 6 (10th March 2015) - Orvananos, Bernardo; Yu, Hui-Chia; Abdellahi, Aziz; Malik, Rahul; Grey, Clare P.; Ceder, Gerbrand; Thornton, Katsuyo
Abstract : Nanoparticles with a tendency to phase separate interact with each other during a process of either intraparticle phase separation (occurring inside the particle) or interparticle phase separation (occurring between particles). In this paper, we examine a half-cell consisting of two particles to systematically analyze the particle interactions and their resulting voltage response at different insertion currents. The kinetics of the interactions between nanoparticles is studied for cases in which particles undergo interparticle and intraparticle phase separation. Our results indicate that the interactions between particles in a cell containing only particles that undergo intraparticle phase separation are similar to those in a cell containing only particles that undergo interparticle phase separation. In both cases, sequential transformation occurs at low currents, whereas a simultaneous transformation occurs at high currents. However, such transformation dynamics changes in cases where the cell contains a mixture of particles that undergo interparticle and intraparticle phase separations, which exhibits more complex dynamics.